2022
DOI: 10.3390/nu14081607
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Impact of Nutritional Supplementation on Osteoarthritis Symptoms

Abstract: Conflicting evidence exists concerning the effects of nutrient intake in osteoarthritis (OA). A systematic literature review and meta-analysis were performed using PubMed, EMBASE, and Cochrane Library up to November 2021 to assess the effects of nutrients on pain, stiffness, function, quality of life, and inflammation markers. We obtained 52 references including 50 on knee OA. Twelve studies compared 724 curcumin patients and 714 controls. Using the standardized mean difference, improvement was significant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 101 publications
0
32
0
2
Order By: Relevance
“…Randomized controlled trials on the effects of vitamin D supplementation on the progression of knee OA and related symptoms were recently summarized in several meta-analysis [103, [107][108][109][110][111] and are presented in Table 3 including various studies [112][113][114][115][116][117][118]. Vitamin D supplementation to patients with 25(OH)D below 50 nmol/L, but not higher, may alleviate pain and improve joint function.…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials on the effects of vitamin D supplementation on the progression of knee OA and related symptoms were recently summarized in several meta-analysis [103, [107][108][109][110][111] and are presented in Table 3 including various studies [112][113][114][115][116][117][118]. Vitamin D supplementation to patients with 25(OH)D below 50 nmol/L, but not higher, may alleviate pain and improve joint function.…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%
“…Vitamin D supplementation to patients with 25(OH)D below 50 nmol/L, but not higher, may alleviate pain and improve joint function. In the review of Mathieu et al [111], 3 studies assessing the effects of 2000 to 3000 IU of vitamin D per day for 1 or 2 years on OA symptoms in more than 500 patients demonstrated that VAS evaluated pain and WOMAC function were significantly improved, albeit with a modest effect size.…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%
“…One of the goals of osteoarthritis pharmacotherapy is to reduce the concentration of inflammatory mediators [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Increased concentrations of inflammatory cytokines, chemokines, and growth factors accumulating in the articular cartilage matrix, and an increased duration of the inflammatory process associated with elevated levels of these factors, are responsible for joint destruction [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin reduces lipogenesis and exerts antipruritic, antiinflammatory, antineoplastic, analgesic, antimicrobial, antifungal, antiviral, and antioxidant effects (14)(15)(16)(17)(18) . In practice curcumin has been widely sold as a phytotherapeutic agent to treat inflammatory bone diseases in canine (19) and human patients (20) . However, its mechanisms and related cell signaling pathways remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%